STEAM: Science, Technology, Engineering, Art, and Mathematics on History Learning in the 21st Century - Lestari, Dea; Ibrahim, Nurzengky; Iriani, Corry (Journal of Education Reseach and Evaluation, 2023)
Implementation of STEAM, both teachers and students, are still a little confused with the concept of STEAM. This article discusses how to apply STEAM and what difficulties educators face when implementing STEAM. This study aims to analyze how the implementation of STEAM in history learning in the 21st century. This study uses qualitative research with a case study research design. Observation data collection techniques, and interviews. The validity of the data was tested through triangulation of sources and using descriptive analysis. The results of this study indicate that STEAM has been applied in history learning. In addition, the implementation of STEAM is an effort to integrate STEAM into one with history learning, by linking the elements of STEAM, so students are given a holistic understanding of the interrelationships of the fields of science through 21st century learning experiences. STEAM is one of the important concepts that must be mastered by history teachers to integrate history material with other sciences, then make students have high thinking and analytical power in the learning process.